2002
DOI: 10.1523/jneurosci.22-19-08379.2002
|View full text |Cite
|
Sign up to set email alerts
|

Group I Metabotropic Glutamate Receptor Signaling via Gαq/Gα11 Secures the Induction of Long-Term Potentiation in the Hippocampal Area CA1

Abstract: Heterotromeric G-proteins of the Gq family are thought to transduce signals from group I metabotropic glutamate receptors (mGluRs) in central neurons. We investigated roles of this cascade in hippocampal long-term potentiation (LTP) by using null-mutant mice lacking the alpha subunit of Gq (Galphaq) or G11 (Galpha11). We found no obvious abnormalities in the morphology, layer structure, expression of NMDA receptors, and basic parameters of excitatory synaptic transmission in the hippocampus of Galphaq mutant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 72 publications
3
25
1
Order By: Relevance
“…In contrast, mGluR activation drives trafficking of GluR mRNAs into dendrites (present study) and promotes local on-site protein synthesis (Kacharmina et al, 2000;Ju et al, 2004). Whereas mGluR activation promotes AMPAR endocytosis and LTD on the order of minutes, mGluR LTD is followed by priming of LTP, a state in which persistent enhanced membrane excitability facilitates LTP induction on the order of hours (Cohen and Abraham, 1996;Cohen et al, 1999;Raymond et al, 2000;Miura et al, 2002). We propose that enhanced levels of GluR mRNAs in dendrites may represent a mechanism relevant to priming.…”
Section: Physiological Significance Of Regulated Trafficking Of Amparmentioning
confidence: 61%
“…In contrast, mGluR activation drives trafficking of GluR mRNAs into dendrites (present study) and promotes local on-site protein synthesis (Kacharmina et al, 2000;Ju et al, 2004). Whereas mGluR activation promotes AMPAR endocytosis and LTD on the order of minutes, mGluR LTD is followed by priming of LTP, a state in which persistent enhanced membrane excitability facilitates LTP induction on the order of hours (Cohen and Abraham, 1996;Cohen et al, 1999;Raymond et al, 2000;Miura et al, 2002). We propose that enhanced levels of GluR mRNAs in dendrites may represent a mechanism relevant to priming.…”
Section: Physiological Significance Of Regulated Trafficking Of Amparmentioning
confidence: 61%
“…A direct relationship between G␣ q/11 dysfunction and the pathogenesis of AD leading to neurodegeneration and dementia is suggested by the important role of G␣ q/11 proteins in neuronal survival and memory (9,10,39,40). In addition, many of the cognitionenhancing effects of acetylcholine in mice are mediated by G␣ q/11 -coupled muscarinic receptors (39).…”
Section: Discussionmentioning
confidence: 99%
“…G␣ q/11 -stimulated signal transduction pathways are important for neuronal communication, synaptic plasticity, and neuronal survival (9,10). Therefore, it is likely that the G␣ q/11 signaling defect of AD patients plays a role in the disease process leading to neurodegeneration and dementia.…”
mentioning
confidence: 99%
“…It is tempting to draw a parallel between these molecular results and LTP induction. Under low stimulation conditions, coactivation of both NMDARs and mGluRs have been reported to be needed for LTP induction (Miura et al, 2002;Kotecha et al, 2003) and that PKC inhibitors but not IP 3 antagonists were shown to block LTP (Fujii et al, 2004).…”
Section: Synergistic Activation Of Pkc␥ After Iglur and Mglur Stimulamentioning
confidence: 99%